Estudo de reatores eletroquímicos para remoção de Cu2+ , Zn2+, Fenol e BTEX em água produzida - Ramalho, Adriana Margarida Zanbotto (2008)
The production of water has become one of the most important wastes in the petroleum industry, specifically in the up stream segment. The treatment of this kind of effluents is complex and normally requires high costs. In this context, the electrochemical treatment emerges as an alternative methodology for treating the wastewaters. It employs electrochemical reactions to increase the capability and efficiency of the traditional chemical treatments for associated produced water. The use of electrochemical reactors can be effective with small changes in traditional treatments, generally not representing a significant additional surface area for new equipments (due to the high cost of square meter on offshore platforms) and also it can use almost the same equipments, in continuous or batch flow, without others high costs investments. Electrochemical treatment causes low environmental impact, because the process uses electrons as reagent and generates small amount of wastes. In this work, it was studied two types of electrochemical reactors: eletroflocculation and eletroflotation, with the aim of removing of Cu2+, Zn2+, phenol and BTEX mixture of produced water. In eletroflocculation, an electrical potential was applied to an aqueous solution containing NaCl. For this, it was used iron electrodes, which promote the dissolution of metal ions, generating Fe2+ and gases which, in appropriate pH, promote also clotting-flocculation reactions, removing Cu2+ and Zn2+. In eletroflotation, a carbon steel cathode and a DSA type anode (Ti/TiO2-RuO2-SnO2) were used in a NaCl solution. It was applied an electrical current, producing strong oxidant agents as Cl2 and HOCl, increasing the degradation rate of BTEX and phenol. Under different flow rates, the Zn2+ was removed by electrodeposition or by ZnOH formation, due the increasing of pH during the reaction. To better understand the electrochemical process, a statistical protocol factor (22) with central point was conducted to analyze the sensitivity of operating parameters on removing Zn2+ by eletroflotation, confirming that the current density affected the process negatively and the flow rate positively. For economical viability of these two electrochemical treatments, the energy consumption was calculated, taking in account the kWh given by ANEEL. The treatment cost obtained were quite attractive in comparison with the current treatments used in Rio Grande do Norte state. In addition, it could still be reduced for the case of using other alternative energy source such as solar, wind or gas generated directly from the Petrochemical Plant or offshore platforms